Awareness of consumer rights and clothing purchase habits of selected consumers - Gatpatan, Kylie Adrienne T.
As per the Department of Trade and Industry, the need for restrictions on online transactions grows along with the number of online enterprises that are starting up in response to the COVID-19 outbreak. Moreso, the DTI takes the drafting of policies seriously in order to guarantee that online retailers have the capability to support online transactions and that customers may make purchases in a safe and secure environment. This descriptive study aimed to examine the awareness of selected consumers on their consumer rights and purchasing habits. The researcher administered a survey questionnaire to 60 selected respondents residing in Metro Manila to determine and understand consumers’ considerations in purchasing clothes online and measure the level of awareness on their consumer rights – Right to Education, Right to Information, and Right to Redress. Based on the findings, the Right to Information recorded the highest level of awareness (81.67%) among the respondents. The study also found out that the main factors considered by most online shoppers are seeing actual photos of clothes, complete description, size chart, and responsiveness of online sellers. The most common issues encountered when shopping online are receiving the wrong size or color and getting a completely different product compared to the image displays. In these instances, the immediate recourse done by the respondents is to contact the seller to request for a refund. The study concludes that the consumers’ shift to online shopping during the pandemic has changed their purchasing behavior and habits which affected how they uphold their rights as consumers.